The influence of difficult child temperament and parenting stress on parental problematic smartphone use in early childhood: a moderated mediation analysis - Schneebeli, Larissa; Braune-Krickau, Katrin; Joliat, Anouk; von Wyl, Agnes (Frontiers in Psychology, 2025)
Smartphone use has become an integral part of daily life and is also common among parents of young children. As parental problematic smartphone use can impact parents’ and children’s well-being, it is important to examine the determinants of this issue. This study examined the association between difficult temperament in toddlers, parenting stress, and parental problematic smartphone use. Results of a moderated mediation analysis utilizing data from 261 mothers and fathers of 14-month-old children showed that parenting stress fully mediated the association between difficult child temperament and parental problematic smartphone use. Parental gender did not moderate the association between parenting stress and problematic smartphone use. Parents who rated their child’s temperament as more difficult reported more parenting stress, which in turn led to higher levels of problematic smartphone use. Parenting stress is thus an important determinant of parental problematic smartphone use. Further research on stress management and parental smartphone use is needed to develop targeted interventions that promote the well-being of parents and children. Parental smartphone use should be considered holistically by taking various influencing factors and their interplay into account rather than examining them in isolation.